Analisis Pengaruh Perputaran Kas dan Perputaran Piutang Terhadap Profitabilitas Usaha Pada Koperasi Kredit Citra Hidup Tribuana Kalabahi Kabupaten Alor - Marteda Olang (Peneliti.net, 2023)
This study aims to determine the effect analysis of cash turnover and accounts receivable turnover on business profitability at the Citra Living Credit Coomperative, Tribuana Kalabahi , Alor Regency. This type of research is quantitative research with data collection techniques, namely observation, interviewis , and documentation. This study uses population secondary data and the sample is the financial resports of the Citra Living Credit Coomperative, Tribuana Kalabahi, Alor Regency in the 2018-2022 period. The statistical method used in this study is multiple linear regression by looking at the significant value of the t test and the significal value of the F test as a benchmark in returning the hypothesis and the results of data processing using the help of the IBM SPSS 25 for windows. The results of this study indicate that: 1) Partially the cash turnover variable has a significant value of 0,000 or 0,0% where this value is smaller thant the alpha value of 0,05 or 5% that the results of this research are Enetima H1 which states thant the cash turnover variable partially has a positive effect on business profitability in the Citra Living Credit Coomperative, Tribuana Kalabahi, Alor Regency. 2) Partially the receivables turnover variabel has a significant value of 0,000 or 0, 0% where this volue is smaller that the alpha value of 0,05 or 5% so that the results of this study accept H2 which states that the receivables turnover variable partially has a positive effect on profitability business at the image of life Credit Coomperative Tribuana Kalabahi Alor Regency. 3)Simultaneously the variables of cash turnover and account receivable turnover have a significant value of 0,000 or 0,0% where this volue is smaller than the alpha value 0,05 or 5% so that the results of this study simultaneously accept H3 which states that the variable cash turnover and receivable turnover simultaneously has a positive effect on business profitability in the Citra Living Credit Coomperative, Tribuana Kalabahi, Alor Regency.